2022
DOI: 10.1002/mds.28990
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Telehealth Services Among People Living With Parkinson's Disease: A Survey Study

Abstract: Background Telehealth has been widely adopted in providing Parkinson's disease care during the coronavirus disease 2019 pandemic. Objective The aim of this study was to survey people living with Parkinson's disease (PwPD) about their attitudes toward and utilization of telehealth services. Methods A survey was administered to PwPD via Parkinson's Foundation and Columbia University mailing lists. Results Of 1,163 responses, 944 complete responses were analyzed. Telehealth awareness was 90.2% (850/942), and util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Although this survey was deployed during the coronavirus pandemic, our findings related to utilization of services was not different from other surveys we pushed in this same time frame ( 20 , 44 ). Although not reported in detail here, a portion of this survey was dedicated to telehealth services.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although this survey was deployed during the coronavirus pandemic, our findings related to utilization of services was not different from other surveys we pushed in this same time frame ( 20 , 44 ). Although not reported in detail here, a portion of this survey was dedicated to telehealth services.…”
Section: Discussioncontrasting
confidence: 62%
“…The study response rate of 29.83% also suggests that respondents may not have been representative of the Veterans living with PD population. Although our sample was <500, our respondent demographics were similar to previous research studies hosted by the Foundation ( 20 , 44 , 45 ). All data in this study were self-reported.…”
Section: Discussionmentioning
confidence: 68%
“…Telehealth/m-health is found to be a potentially low-cost and efficient element within healthcare treatment programs [ 69 , 70 ], and both patients and caregivers are generally positive to these forms of treatment [ 69 71 ]. This also includes people with PD who in one study responded that telehealth was convenient, easy to use, had the potential to give the same quality of follow-up care as in-person visits, and that telehealth could make follow-up easier in cases were traveling was problematic [ 71 ]. Even though the transition to more digital solutions was already established, the recent pandemic has accelerated the development of digital health care [ 71 74 ], increasing the relevance of these types of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This also includes people with PD who in one study responded that telehealth was convenient, easy to use, had the potential to give the same quality of follow-up care as in-person visits, and that telehealth could make follow-up easier in cases were traveling was problematic [ 71 ]. Even though the transition to more digital solutions was already established, the recent pandemic has accelerated the development of digital health care [ 71 74 ], increasing the relevance of these types of interventions. A monthly digital follow-up on physical activity, exercise, and nutrition, might make long-term follow-up more accessible and less time-consuming for individuals, potentially reducing costs to society [ 69 ] and hopefully improving long-term self-management in people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions in medical care accompanied by an increase in distress 5 and social isolation 6 have contributed to a rising disease burden for PwP. Telemedicine approaches have been shown to provide appropriate medical care for PwP while complying with pandemic‐related contact restrictions 7,8 . However, this technology has not been universally implemented and may therefore, not be available to all PwP 3,9 …”
mentioning
confidence: 99%